Art at the edges of materiality - Conradi, Ina. (2013)
This paper discusses digital artwork that through the act of creation investigates and integrates emotive subjective abstract imagery in digital and traditional forms. The areas covered are the art of experimental non-narrative animation, 3D stereo and large-scale algorithmic-based painting and prototyping for interactive and digitally fabricated art installations and performances. The paper’s intention is to interpret a complex body of digitally generated artwork that attempts to integrate animation, fine art painting and scientific inquiry through artist practice as pursued through the process of academic research. The outcome of is collaborative works done at the Nanyang Technological University, School of Art Design and Media. The overall aim is in better understanding of the fine art process and mutual influences that various and often opposed disciplines have in collaborative projects where emotion-based interaction is important.